Jason Dixon’s Personality Development as Seen in Martin McDonagh’s Three Billboards Outside Ebbing, Missouri (2017) - Risky Shasita; Linda Hudawinata (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2021)
This paper is aimed to reveal the personality development of Jason Dixon as seen in Martin McDonagh’s Three Billboards Outside Ebbing, Missouri (2017). The change of Dixon personality made the researcher interested in analyzing the personality dynamic. In analyzing the data, the study uses descriptive qualitative methods. The data is collected through data collection techniques from the dialogue and any related data from outside the movie. After the data are collected, the researcher then reads, classifies, identifies, and selects the data. This study relies on Psychological literature theory and psychoanalysis by Sigmund Freud as the theoretical framework. Through the analysis we found out Dixon psychological changes from his id which is him respecting his senior, Bill Willoughby and it triggers his ego to do violence to people whom he thought has been involved in the billboard project that is to confront Bill Willoughby. However, as the movie goes by his personality changed because of his superego that is the letter from Bill Willoughby that shifted his moral.